Cartoon-style Foolishness. Nonsense Forms in Viaje olvidado [Forgotten Journey] by Silvina Ocampo - Biancotto, Natalia (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This paper analyzes nonsense forms in Viaje olvidado [Forgotten Journey], Silvina Ocampo ́s first book. In these stories, a radical disregard for rational and common sense leads to the appearance of a insane world in which childhood and nonsense are linked. Certain events are narrated with a superficiality, lack of emotion and indifference that introduce a humorous twist to the story, bursting into the logic of cartoon. Humor marks the passage from sense to nonsense, as these unprecedented bursts disrupt the relationship with language.